Histones Methyltransferase NSD3 Inhibits Lung Adenocarcinoma Glycolysis Through Interacting with PPP1CB to Decrease STAT3 Signaling Pathway - Yanling Zhou; Xintong Peng; Cheng Fang; Xin Peng; Jianing Tang; Zuli Wang; Yao Long; Jielin Chen; Yuanhao Peng; Zewen Zhang; Yanmin Zhou; Jun Tang; et al. (Advanced Science)
Abstract Histones methyltransferase NSD3 targeting H3K36 is frequently disordered and mutant in various cancers, while the function of NSD3 during cancer initiation and progression remains unclear. In this study, it is proved that downregulated level of NSD3 is linked to clinical features and poor survival in lung adenocarcinoma. In vivo, NSD3 inhibited the proliferation, immigration, and invasion ability of lung adenocarcinoma. Meanwhile, NSD3 suppressed glycolysis by inhibiting HK2 translation, transcription, glucose uptake, and lactate production in lung adenocarcinoma. Mechanistically, as an intermediary, NSD3 binds to PPP1CB and p‐STAT3 in protein levels, thus forming a trimer to dephosphorylate the level of p‐STAT3 by PPP1CB, leading to the suppression of HK2 transcription. Interestingly, the phosphorylation function of PPP1CB is related to the concentration of carbon dioxide and pH value in the culture environment. Together, this study revealed the critical non‐epigenetic role of NSD3 in the regulation of STAT3‐dependent glycolysis, providing a piece of compelling evidence for targeting the NSD3/PPP1CB/p‐STAT3 in lung adenocarcinoma.